Influence of initial residual stresses on welding residual stresses in ultra-high strength steel S960 - Sun, Jiamin; Dilger, Klaus (Journal of manufacturing processes, 2023)
In general, the as-received steel components before welding have usually suffered from numerous manufacturing processes. There is no doubt that initial residual stresses (IRS) remain in the steels with different magnitudes and even signs if no any stress-relieving process is applied before welding. Nevertheless, the relationship between IRS and welding residual stresses (WRS) is still not unclear yet, especially in ultra-high strength steels (UHSS). The current work aims to elucidate the influence of IRS on WRS in ultra-high strength steel S960. The X-ray diffraction (XRD) was applied to measure both IRS and WRS here. The experimental results exhibit that IRS in the weld area are completely eliminated because of the metallurgical and mechanical melting effect, which have no influence on WRS. In the heated zone out of the weld area, initial longitudinal residual stress (σRSL) can significantly affect welding σRSLonly if it is in tension. In the cold area, WRS are the combination of IRS and welding-induced residual stresses (WIRS). Furthermore, IRS play the dominant role here in general. No matter how much and what sign IRS are in the cold area, IRS here almost have no impact on WRS in the weld area.